Epidemiological And Microbiological Profile of Patient’s Having Microbial Keratitis - Patel, Saurabh; Chaudhari, Akshay M; Solu, Trupti M; Gharat, Vaibhav (National Journal of Community Medicine, 2014)
Background: Microbial keratitis is common potentially sight threatening ocular infection that may be caused by bacteria, fungi or virus. Epidemiological and microbiological profile of corneal ulceration have been found vary with patient population, health of cornea, geographical location and climate tends to vary over times. Methods: The present cross-sectional study was conducted 3 on patients having microbial keratitis. Detailed history taking include duration of symptoms, predisposing factors, history of trauma, traumatic agents, associated ocular conditions, other systemic disease, treatment received prior to presentation, visual acuity at the time of presentation and all clinical findings were collected. Detailed ocular examination, using standard technique, corneal scraping were also taken under aseptic conditions from each ulcer. Results: In our study, 51 cases belonged to low socio-economic group of which 21 cases (41%) of bacterial keratitis, 15 cases (29%) of fungal keratitis , 11 cases (21%) of viral keratitis and 4 cases (8%) of Mixed (bacterial + fungal ) keratitis. A total 15 bacterial pathogens were isolated from the 64 eyes which yielded only bacterial growth in culture. Out of which 4(16%) were staphylococcus aureus, 4(16%) pseudomonas,3(12%) were streptococcus,2(8%) were staphylococcus epidermis. A total of 17 viral keratitis 9(53%) were recurrent cases. Conclusion: Trauma is most common predisposing factor responsible for microbial keratitis. Direct microscopic examination of corneal scraping is key tool for rapid diagnosing and institution of antimicrobial therapy.